FUTSAL: Dominant Technique at Provincial Sports Week 2022 - Ramadhan, Chairul Umam; Bakhri, Rafdlal Saeful; Irawan, Debi Krisna; Hamdani, Muhamad Raihan (Musamus Journal of Physical Education and Sport (MJPES), 2024)
Objective. of this study is to identify the predominant tactics utilized during the 2022 provincial sports week. Materials and Methods. The research approach employed in this study is a quantitative method, by observing the match using YouTube social media. The population in this study was the 2022 West Java Porprov Team, the sample was taken purposively. A frequency test was conducted to identify the most commonly employed techniques. This study employs a video-based observation method that yields objective data and utilizes a frequency test to present statistics on dominant futsal techniques. However, the limitations of this study lie in observations via video which may not capture all features of the approach entirely and the tiny sample from one event (Porprov), making it impossible to generalize. Results. The study's results indicated that passing techniques were employed 982 times, control 932 times, shooting 245 times, dribbling 233 times, chipping 185 times, heading 49 times, and turning 28 times, with the respective usage percentages being 35% for passing, 37% for control, 9% for shooting, 9% for dribbling, 7% for chipping, 2% for heading, and 1% for turning. Conclusion. Passing and control methods are the predominant strategies employed in futsal matches at the 2022 Provincial Sports Week. Subsequent researchers are advised to employ multi-shot video analysis and conduct comparisons with other competitions for more comprehensive results. This study aims to offer guidance for futsal coaches and players to emphasize passing and control tactics in training, as these skills are predominantly utilized in provincial level matches.